Effect of sandblasting on the characterization of 95MXC coating layer on 304 stainless steel prepared by the twin wire arc spray (TWAS) coating method - Deni Fajar Fitriyana; Windy Desti Puspitasari; Agustinus Purna Irawan; Januar Parlaungan Siregar; Tezara Cionita; Natalino Fonseca Da Silva Guteres; Mateus De Sousa Da Silva; Jamiluddin Jaafar (Mechanical Engineering for Society and Industry, 2024)
Twin wire arc spraying (TWAS) is a thermal spray process that is widely used in various industries. Nevertheless, the impact of repeated sandblasting on the coating characteristics of FeCrBSiMn coating created using the TWAS technique has not been extensively researched. Therefore, this study aims to investigate the influence of repeated sandblasting on the properties of the FeCrBSiMn coating layer created using the TWAS process. The study used stainless steel 304, 75B, and FeCrBSiMn as the substrate, bond coat, and top coat materials. The substrate materials underwent sandblasting with a repetition of 1, 2, and 3 cycles before the coating procedure. The coating's quality in this study was assessed using surface roughness, thickness, hardness, corrosion rate, bond strength, and Scanning Electron Microscope (SEM) examination. The findings of this investigation indicate that the sandblasting treatment substantially elevates the surface roughness of 304 stainless steel substrates. As the substrate surface becomes rougher, there is an increase in the percentage of porosity and unmelted material, as well as an increase in the thickness of the coating layer. Furthermore, the hardness of the resulting coating layer diminishes. Specimen A exhibited superior qualities in comparison to the other specimens. The coating layer on this specimen has a percentage of unmelted material and porosity, thickness, hardness and adhesion of 7.122%, 0.125 mm, 1081.6 HV and 14.5 MPa respectively. This investigation's results indicate that the substrate material's corrosion rate (x 10−6 mmpy) is 3648.6, which is lower than the corrosion rate of specimen A, which is 37.802.